2015
DOI: 10.1186/s12968-015-0211-4
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular fluid kinetic energy time curves in heart failure from cardiovascular magnetic resonance 4D flow data

Abstract: BackgroundMeasurement of intracardiac kinetic energy (KE) provides new insights into cardiac hemodynamics and may improve assessment and understanding of heart failure. We therefore aimed to investigate left ventricular (LV) KE time curves in patients with heart failure and in controls.MethodsPatients with heart failure (n = 29, NYHA class I-IV) and controls (n = 12) underwent cardiovascular magnetic resonance (CMR) including 4D flow. The vortex-ring boundary was computed using Lagrangian coherent structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 29 publications
11
93
2
Order By: Relevance
“…Multiple 4D flow MRI studies showed that patients with LV dysfunction present altered flow patterns through the LV with impaired preservation of inflow KE to the end of diastole and altered KE-time curves (the amount of KE inside the LV during each time step over the total cardiac cycle) [4,6,7,21], even in patients with normal to mild LV remodeling and normal to mildly depressed LV systolic function [7]. These KE changes in the LV could be a valuable diagnostic marker to evaluate diastolic function and might be useful for early detection of deteriorating ventricular function [1, 4-7, 21, 22], which could reduce patient morbidity and mortality [23].…”
Section: Kinetic Energy (Ke) Over LV Diastolementioning
confidence: 99%
See 2 more Smart Citations
“…Multiple 4D flow MRI studies showed that patients with LV dysfunction present altered flow patterns through the LV with impaired preservation of inflow KE to the end of diastole and altered KE-time curves (the amount of KE inside the LV during each time step over the total cardiac cycle) [4,6,7,21], even in patients with normal to mild LV remodeling and normal to mildly depressed LV systolic function [7]. These KE changes in the LV could be a valuable diagnostic marker to evaluate diastolic function and might be useful for early detection of deteriorating ventricular function [1, 4-7, 21, 22], which could reduce patient morbidity and mortality [23].…”
Section: Kinetic Energy (Ke) Over LV Diastolementioning
confidence: 99%
“…In acquired heart disease, remodelling occurs which can lead to alterations in intracardiac hemodynamics [4]. Alteration in intraventricular KE derived from 4D flow MRI has been used to assess left ventricular (LV) and right ventricular (RV) (dys)function in patients with different stages of heart failure (HF) [4][5][6][7]. This is also the case in various congenital heart diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with heart failure ( n  = 29, NYHA class I-IV) and controls ( n  = 12) underwent 4D flow CMR [165]. The authors used a quantitative approach to global LV performance as defined by the kinetic energy within the LV volume across the cardiac cycle and separated volume into regions defined by vortical or non-vortical flow across a range of left ventricular function.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Quantification of blood flow using volumetrics and velocity information have led to formulation of advanced hemodynamic markers of cardiovascular function, such as kinetic energy (24,126,130,(138)(139)(140)(141)(142), turbulent kinetic energy (95,131,134,143,144), calculation of pressure gradients (145,146), wall shear stresses (147) and hemodynamic forces (148).…”
Section: D Flow Cmrmentioning
confidence: 99%